Humoral immunity in Hansen’s Disease - Cossermelli-Messina, Waldenise; Cossermelli, Wilson (São Paulo Medical Journal, 1995)
For many years immune response in leprosy has been studied. Since 1960 several reports dealing with humoral immunity have been described in the literature. Different autoantibody rates occur in leprosy. There is an increase in the prevalence of autoantibodies in elderly patients with long standing disease, in lepromatous leprosy and in those with reactional states. The diferences in rates among various studies are attributed to different methods and variations among patient samples concerning age, gender, polar forms, therapy and other elements. The prevalence of numerous antibodies, immune complexes, cryoglobulins and complement levels have been studied by many authors. This also highlights the importance of the more recent reviews of anti-Mycobacterium leprae glycolipid antibodies such as the anti-phenolic glycolipid-I antibodies in which titers are variable and depend on genetic factors.